2014
DOI: 10.1007/s11011-014-9591-7
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonist liraglutide reverses long-term atypical antipsychotic treatment associated behavioral depression and metabolic abnormalities in rats

Abstract: Mood disorder patients that are on long-term atypical antipsychotics treatment frequently experience metabolic dysfunctions. In addition to this, accumulating evidences points to increased risk of structural abnormalities, brain volume changes, altered neuroplasticity and behavioral depression with long-term antipsychotics use. However, there is paucity of preclinical evidences for long-term antipsychotic associated depression-like behavior. The objectives of the present study were: (1) to evaluate influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Systemic insulin resistance may do so through hyperglycaemia and its consequences [10], microvascular disease, chronic inflammation, and dysfunction of the blood brain barrier, which may be compounded by associated comorbidities such as hypertension, dyslipidaemia and renal impairment [51]. Local brain insulin resistance may act via protein deposition and aggregation, and failure of clearance mechanisms, independent of systemic insulin resistance [51,53].…”
Section: Common Pathogenic Mechanisms Of Systemic and Brain Insulin Rmentioning
confidence: 99%
“…Systemic insulin resistance may do so through hyperglycaemia and its consequences [10], microvascular disease, chronic inflammation, and dysfunction of the blood brain barrier, which may be compounded by associated comorbidities such as hypertension, dyslipidaemia and renal impairment [51]. Local brain insulin resistance may act via protein deposition and aggregation, and failure of clearance mechanisms, independent of systemic insulin resistance [51,53].…”
Section: Common Pathogenic Mechanisms Of Systemic and Brain Insulin Rmentioning
confidence: 99%
“…For example, in animal models GLP1R agonists attenuate condition place preference for cocaine; mitigate the effects of alcohol and amphetamine; demonstrate neuroprotective activity in Alzheimer's and Parkinson's diseases; and show direct antipsychotic-like effect comparable to haloperidol (Erreger et al, 2012;Graham et al, 2013;Holscher, 2014;Dixit et al, 2013). Recently, Sharma and colleagues demonstrated that the GLP1R agonist liraglutide can ameliorate some of the negative metabolic and behavioral effects of olanzapine treatment in rats (Sharma et al, 2014a). Finally, the DPP-IV inhibitor sitagliptin, which increases GLP1 concentrations by slowing GLP1 breakdown by DPP-IV, extends the time to tolerance of the anxiolytic effect of ethanol and delays onset of ethanol withdrawal induced anxiety in rats (Sharma et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that GLP-1Rs are observed in brain regions related to energy balance and regulation of moods, such as the amygdala, hippocampus, and dorsal raphe nucleus (Merchenthaler et al, 1999). Some studies have also shown the presence of GLP-1Rs in mood-related brain regions and demonstrated its powerful role in emotional processing within the CNS (Merchenthaler et al, 1999;Sharma et al, 2015).…”
Section: Neurotransmitter Imbalance In Depression and Its Relation Tomentioning
confidence: 98%